2018
DOI: 10.1007/s10995-018-2559-1
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerable Women’s Perceptions of Individual Versus Group Prenatal Care: Results of a Cross-Sectional Survey

Abstract: Introduction Vulnerable pregnant women (e.g. women with low socio-economic status or recent immigrants) are less likely to receive adequate prenatal care or to attend perinatal education classes. CenteringPregnancy (CP) is a model of group prenatal care which combines assessment, education and support. This study aimed to assess patient experience among vulnerable women in group prenatal care compared to individual care. Methods Women participating in CP at a community-based health centre in urban Alberta were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…To further decrease perinatal HIV transmission by improving consistent prenatal care and improve long term maternal health, group prenatal care should be considered an option with significant benefits. n (18) .003…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further decrease perinatal HIV transmission by improving consistent prenatal care and improve long term maternal health, group prenatal care should be considered an option with significant benefits. n (18) .003…”
Section: Resultsmentioning
confidence: 99%
“…MATERNAL Original Research studies have reported improvement in social support, especially in women with more psychosocial stress at entry to care, 16,17 whereas others reported no change. 11,18 Similarly, studies in adolescents 19 and women with increased psychosocial stress 20 reported improvement in depressive symptoms with participation in group care, whereas others reported no difference. 11,16,17,21 In terms of specific disease-adapted group prenatal care, a recent randomized clinical trial for women living with diabetes reported higher levels of social support as a result of the intervention but did not report a significant difference in baseline, 38-week, or postpartum EPDS scores.…”
Section: Study Populationmentioning
confidence: 99%
“…The evidence in this field is building, with studies indicating improvements in preterm birth and low birth weight, 36 maternal knowledge and patient satisfaction, [37][38][39] social support 40 and reduced costs of healthcare provision. 41 However, a Cochrane systematic review including four randomised and quasi-RCTs (n=2350, English speaking women) evaluating group antenatal care found no clear evidence of improvement in rates of preterm birth, low birth weight, small-for-gestational age infants or perinatal mortality comparing group-based models of antenatal care with one to one antenatal care.…”
Section: Gpc For Women and Their Families From A Refugee Backgroundmentioning
confidence: 99%
“… 3–5 Regarding satisfaction with care on the other hand, research shows that satisfaction is greater among women who receive GANC. 3 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Regarding satisfaction with care on the other hand, research shows that satisfaction is greater among women who receive GANC. 3,6 GANC offers an alternative to traditional individual care, which is still the predominant model in most Western countries. 7 Standard antenatal care entails individual visits with a healthcare provider, such as an obstetrician, a midwife, or a GP in a hospital or another clinical setting.…”
Section: Introductionmentioning
confidence: 99%